Audit Delay Analysis Based on Audit Effort, Earning Per Share and Audit Opinions Before and During the Covid-19 Pandemic - Amyar, Firdaus; Nahrowi, Abdul Fatah (Institut Bisnis dan Informatika Kesatuan, 2022)
The audit process is complex and requires a lot of resources causing audit delays resulting in delays in submitting financial reports. The COVID-19 pandemic adds challenges to the audit process. This research aims to determine the effect of audit effort, earnings per share, and audit opinion on audit delay with financial distress as a moderating variable. This research method uses secondary data with a quantitative approach where the sample selected in this research uses a purposive sampling technique. The population of mining sector companies registered on the IDX was 43 companies which were then eliminated to become 25 companies with a research period of 4 years, so there were 100 samples. The testing of data and hypotheses is separated between conditions before the COVID-19 pandemic (2018-2019) and conditions during the COVID-19 pandemic (2020-2021). The research results show that audit efforts had a negative and significant impact on audit delays before the COVID-19 pandemic. On the other hand, audit efforts have a positive impact on audit delays during the pandemic. Earnings per share had a negative impact on audit delays before and during the COVID-19 pandemic. Audit opinion has no effect on audit delays before and during the COVID-19 pandemic. Financial tensions moderated the influence of audit effort on audit delays before and during the COVID-19 pandemic, but financial tensions during the pandemic were unable to moderate the influence of audit effort on audit delays.